An Adaptive Virtual Training System Based on Universal Design. Issue 34 (2019) - Loch, Frieder; Fahimipirehgalin, Mina; Czerniak, Julia N.; Mertens, Alexander; Villani, Valeria; Sabattini, Lorenzo; Fantuzzi, Cesare; Vogel-Heuser, Birgit
Abstract: The increasing complexity of manufacturing environments requires effective training systems to prepare the operation personnel for their tasks. Several training systems have been proposed. A common approach is the application of virtual environments to train interactions with an industrial machine in a safe, attractive, and efficient way. However, these training systems cannot adapt to the requirements of an increasingly diversified workforce. This paper introduces an approach for the design of an adaptive virtual training system based on the idea of universal design. The system is based on a two-step approach that consists of an initial adaptation to the user capabilities and real-time adaptations during training based on measurements of the user. The adaptations concern the use of different representations of lessons with different complexity and interaction modalities. The proposed approach provides a flexible training system that can adapt to the needs of a broad group of users.